Medical claims paid by workers' compensation insurance among US Medicare beneficiaries, 1999–2016. Issue 3 (11th January 2021) - Kurth, Laura; Casey, Megan; Chin, Brian; Mazurek, Jacek M.; Schleiff, Patricia; Halldin, Cara; Blackley, David J.
Abstract: Background: Workers' compensation claims among Medicare beneficiaries have not been described previously. To examine the healthcare burden of work‐related injury and illness among Medicare beneficiaries, we assessed the characteristics, healthcare utilization, and financial costs among Medicare beneficiaries with claims for which workers' compensation was the primary payer. Methods: We extracted final action fee‐for‐service Medicare claims from 1999 to 2016 where workers' compensation had primary responsibility for claim payment and beneficiary, claim type, diagnoses, and cost information from these claims. Results: During 1999–2016, workers' compensation was the primary payer for 2, 010, 200 claims among 330, 491 Medicare beneficiaries, and 58.7% of these beneficiaries had more than one claim. Carrier claims submitted by noninstitutional providers constituted the majority (94.5%) of claims. Diagnosis codes indicated 19.4% of claims were related to diseases of the musculoskeletal system and connective tissue and 12.9% were related to disease of the circulatory system. Workers' compensation insurance paid $880.4 million for these claims while Medicare paid $269.7 million and beneficiaries paid $37.4 million. Conclusions: Workers' compensation paid 74% of the total amount to providers for these work‐related medical claims among Medicare beneficiaries. Claim diagnoses were similar to those of all workers' compensation claims in the United States. Describing these work‐related claims helps identify the healthcare burden due to occupational injury and illness among Medicare beneficiaries resulting from employment and identifies a need for more comprehensive collection and surveillance of work‐related medical claims.